VD_FINDINFO Faillite / 2020 / 19 vom 6. April 2020 - VD Tribunal cantonal (2020)
SOCIÉTÉ À RESPONSABILITÉ LIMITÉE, AJOURNEMENT DE LA FAILLITE, ASSAINISSEMENT FINANCIER | 725a al. 1 CO, 820 CO, 174 al. 1 LP, 192 LP